Desenvolvimento de uma formulação farmacêutica para uso tópico, análise fitoquímica e farmacológica de Persea americana Mill. (Lauraceae) - Deuschle, Viviane Cecilia Kessler Nunes (2018)
The species Persea americana Mill., belonging to the Lauraceae family is known in popular medicine as avocado. Several pharmacological effects attributed to this species have been described in the literature, especially antioxidant, anti-inflammatory, antimicrobial and analgesic activity. The objective of this work was to perform a phytochemical evaluation in the leaves extract of P. americana and to evaluate its antioxidant capacity and antimicrobial activity, as well as to develop a topical pharmaceutical formulation, evaluate its antinociceptive and anti-inflammatory effect, determine physical chemistry stability, the antioxidant effect, and the active substance releasing from the formulation. The leaves of P. americana were dried and crushed and subjected to hydroethanolic maceration and later to fractionation using solvents of increasing polarity (chloroform, ethyl acetate and n-butanol). Two gel formulations containing 1% and 3% of the hydroethanolic extract were developed. The chemical constituents identified in the hydroethanolic extract and in the fractions (with the exception chloroform fraction) were chlorogenic acid, rutin and quercetin. The following phenolic compounds too were detected in the hydroethanolic extract: chlorogenic, cafeic, ferulic, vanilic and hydroxybenzoic acids, besides the flavonoids catechin, rutin, quercetin and kaempferol. The hydroethanolic extract and ethyl acetate and butanolic fractions presented antifungal activity and only ethyl acetate showed antimycobacterial activity. The formulation showed antinociceptive activity, but not anti-inflammatory activity in a model of UVB- induced sunburn in mice. The formulations preserved at refrigerator remained more stable during the stability test period. The formulation containing 3% of the extract of P. americana more rapidly released the formulation rutin during the active substance release assay. Both the extracts and the formulation presented antioxidant activity. It can be concluded that P. americana presents actions beneficial to human health and that the chemical constituents found are responsible for these properties.